The Absurdity of Existence: Analyzing Human Relationships in Sartre's No Exit - Abdalla, Shabaz; Mohammed, Rebwar Zainalddin; Ahmad, Hedayat Muhamad (SUAR BETANG, 2024)
This article explores the philosophical concepts of existentialism and absurdism, focusing on the works of Jean-Paul Sartre and Albert Camus. It begins by examining Sartre's notion of "for-itself" and "in-itself," highlighting the inherent discomfort and isolation of human existence, which resonates with Martin Heidegger's idea of "Dasein." The study delves into the fundamental aims of absurdism, which seeks to reconcile the contradictions between human will and a hostile environment. By analyzing Sartre's play No Exit, the article illustrates how absurdist theatre employs non-linear narratives to evoke feelings of disorientation and absurdity, ultimately reflecting on the quest for meaning in a seemingly meaningless world. The study also critiques the absence of Grice's Cooperative Principle, particularly the Maxim of Quantity, in the dialogues of No Exit, emphasizing the complexities of communication in existential contexts. The findings underscore the interplay between existential themes and absurdist techniques, offering insights into the human condition and the perpetual struggle for purpose amidst existential despair. This article is relevant for readers interested in philosophy, theatre, and the exploration of human existence.